Peak VO2 and ventilatory threshold of male college basketball players: A sport-specific protocol for prediction, evaluation and application - Duscha, B. D.; Bennett, W. C.; Fonseca, J.; Potter, N.; Belski, K. N.; Reaves, M. A.; Coyne, B. J.; Amendola, A.; Baggish, A. L.; Kraus, W. E. (Physiological Reports, 2025)
Although basketball is not an endurance sport, a high level of peak oxygen consumption (peak VO2) and ventilatory threshold (VT) are beneficial. Currently, no validated cardiopulmonary exercise test (CPET) protocols exist for basketball. This study developed and validated a basketball-specific CPET protocol and describes the fitness measures. Sixty treadmill CPET's were performed on NCAA Division 1 basketball players. The first 30 CPET's created a prediction equation for peak VO2, and the second 30 tested the validity of the equation. The equation, y = 2.70x + 24.84; r2 = 0.995, predicted peak VO2. Mean relative peak VO2 was 54.1 ± 4.6 mL min-1 kg-1. Mean relative VO2 at VT was 37.8 ± 5.8 mL min-1 kg-1, and heart rate (HR) at VT was 155.1 ± 14.2 bpm. These corresponded to 70.1 ± 10.7% of peak VO2, and 81.4 ± 6.3% of peak HR values. This equation can accurately determine oxygen consumption when direct metabolic testing is not available. The measures of peak VO2, VT, and HRs can be used to assess player fitness, design training protocols, and potentially help explain in-game performance. Additional research is needed to fully establish the relationship between CPET values and basketball performance.